The urgency distribution of an accident and emergency department's workload. Issue 4 (December 1986) - Fitzgerald, G J; Robertson, C E; Little, K; Dove, A F
Abstract : The perceived urgency of 2000 consecutive patients attending the Accident and Emergency Department of the Royal Infirmary, Edinburgh, was assessed using a Linear Analogue Scale. Each patient was assessed by the receptionist, the receiving nurse and the treating doctor. The distribution of urgency rating produced for this patient group was shown to be comparable for each status of assessor, and to correlate with other outcome criteria such as admission and referral rates. The linear scale was also shown to correlate with retrospective assessment using a time-guided category scale. The accident and emergency department workload is predominantly of low urgency (90% less than 5 on a 0-10 scale). Older patients tend to have higher urgency ratings than younger patients and those referred by ambulance, either via general practitioner or 999 calls, have similarly higher urgency distributions. This study provides a basis for the development of a guided category scale for functional triage of accident and emergency departments. Other scoring systems have attempted to similarly quantify the medical component of the workload (Coira & Rothstein, 1983; Peel et al., 1962). However, the complexity of many of these scales, together with the difficulty in usage of so many different scales, begs a reappraisal of the overall triage of patients attending the emergency department. The aim of this study was to look at the perceived urgency distribution of patients presenting to the emergency department. We wished to compare the relative assessment of urgency by various levels of treating staff and to compare those assessments with the referral and outcome of these patients to provide the basis for the development of a comparative Triage Scale.